2011
DOI: 10.1162/glep_a_00072
|View full text |Cite
|
Sign up to set email alerts
|

Jumping on the Human Rights Bandwagon: How Rights-based Linkages Can Refocus Climate Politics

Abstract: This paper makes a normative argument for the greater strategic utilization of human rights institutions, practices, and discourses by those seeking a robust response to climate change. Bandwagoning between these two regimes is hardly a new thing. The environmental movement has long looked to the human rights movement for ideas and support, and vice versa. Here, we argue that there is potential for even more explicit bandwagoning in ways that will most directly benefit those who are suffering, and will continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Bandwagoning of issues is another form of framing, which is used to draw attention to a social issue [30,31]. Consequently, one would expect that this is done only when the connection is positive, but in our research we have found that human trafficking was also linked to more difficult topics such as migration.…”
Section: Competing For Attentionmentioning
confidence: 64%
See 1 more Smart Citation
“…Bandwagoning of issues is another form of framing, which is used to draw attention to a social issue [30,31]. Consequently, one would expect that this is done only when the connection is positive, but in our research we have found that human trafficking was also linked to more difficult topics such as migration.…”
Section: Competing For Attentionmentioning
confidence: 64%
“…For example, linking human rights issues with women's rights has proven to be a powerful framework that has mobilized international support [4]. Nicholson and Chong [30] call this process of linking topics together as "bandwagoning". Actors will assess the social issue by considering possible linkages between the topic of concern and established human rights concerns [31].…”
Section: Human Rights Issuesmentioning
confidence: 99%
“…the emerging academic, judicial and political debate on human rights impacts of climate change. In this sense, the linkage between human rights arguments and climate politics could be considered as 'bandwagoning' providing AOSIS with some moral principles (within a broader climate justice frame) against which the performance of the climate regime would be judged (Nicholson and Chong 2011). 14 But which additional drive could actually be expected from this linkage?…”
Section: Aosis's Options For Frame Alignment Of Climate Politics and mentioning
confidence: 99%
“…Nevertheless, the blame-and-shame effect associated with the declaration of human rights violations exerts some influence on states and concurs to make the normative frame of human rights "real" (Nicholson and Chong 2011).…”
Section: (Ilo Convention 169)mentioning
confidence: 99%